Tris(1,10-phenanthroline)sodium 2,4,6-trimercapto-1,3,5-triazin-1-ide - Marek, Jaromír; Kopel, Pavel; Trávnícek, Zdenek (Acta crystallographica. Section C, Crystal structure communications, 2003)
The title compound, [Na(C(12)H(8)N(2))(3)](C(3)H(2)N(3)S(3)), contains an Na(+) centre which is ionicly bonded to three 1,10-phenanthroline (phen) ligands and one trithiocyanurate(1-) (ttcH(2)) anion. In the crystal structure, the anions are linked via hydrogen bonds to form linear chains. The S and H atoms of the ttcH(2) anion participate in intermolecular N-H.S hydrogen bonding, with N.S distances of 3.298 (2) and 3.336 (2) A. The phen ligands are almost parallel, with dihedral angles of 3.92 (5), 11.75 (5) and 15.45 (5) degrees; moreover, they are nearly perpendicular to the ttcH(2) chains, with angles of 81.94 (7), 85.86 (7) and 85.96 (7) degrees.